(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The study aims to estimate flood risks in Qaws wadi basin south of Jeddah City by determining volumes and peak discharge of floods using the National Resources Conservation Service-Curve Number (NRCS-CN) model of Soil Conservation Service. To achieve this aim, the study followed a methodology that gradually began by collecting data for the model application, starting with the Landsat (9) image and the soil map. Data on severe rainstorms and soil moisture are also obtained from the NASA website and Earth Climate Data. The next step was to process these data in order to obtain the Land Use/Land Cover (LULC), the hydrological groups soil in basin, the distribution of storm rains and soil moisture. Thus, the study involves deriving the (CN) values by merging the two layers of LULC, and the hydrological soil groups. Then, the required equations are applied as potential maximum retention of water by the soil, and initial abstraction before the start of runoff. Thus, the risks of floods are estimated by applying equations of depth, volume and peak discharge of surface runoff based on the most severe rainstorm that the basin was exposed to in 2022. The results of study show that the depth of surface runoff in the basin resulting from the average of 2022 rainstorm, which reached 157.1 mm ranging from 58.59 mm representing 37.3% of the total storm rainfall converted into surface runoff in the vegetation cover areas within soil hydrological group (A), to 151 mm representing 96.15% of the total storm rainfall in the road areas within different types of the soil hydrological groups, with a spatial average at basin level of 118.06 mm, 75.15% of total rainfall of this storm converted into runoff. The surface runoff volume ranges from 246,075 m3 in the vegetation areas within group (A), to 2,549,567 m3 in the sediment areas within group (B), with a spatial average at the basin level of 512,853.17 m3. The peak discharge ranges from 9.74 m3/s in areas where the vegetation distribution matches the hydrological soil group (A); to 100,851.3 m3/s in areas where the sediment distribution matches the hydrological soil group (B); with a spatial average at the basin of 20,286.56 m3/s.